Emotional Intelligence Instruments Used in Health Care Education - Pienimaa Anne; Haavisto Elina; Talman Kirsi (SLACK INC, 2023)
Background: This article aims to describe the content and the psychometric properties of emotional intelligence instruments used in health care education and to examine the relationship between emotional intelligence and study success.
Method: Six electronic databases were searched in spring 2020. Two researchers participated in the selection and quality assessment of the articles. Ultimately, 26 articles were included in the review.
Results: From the included articles, 18 emotional intelligence instruments were identified. The content of the instruments focused on perception of emotions, understanding of emotions, emotional expression, managing emotions, using emotions, and social awareness and relations. In most of the studies, emotional intelligence was related to study success.
Conclusion:The assessment of several important components of emotional intelligence was identified. Comprehensive assessment using the emotional intelligence total score seemed to be the best predictor of study success.